Exploring motivations and resistances for implementing shared decision‐making in clinical practice: A systematic review based on a structure-process-outcome model - Changhai Tang; Anqi Wang; Jingjing Yan (Wiley, 2022)
Abstract Objective Shared decision‐making (SDM) as a multicollaborative approach is vital for facilitating patient‐centred care. Considering the limited clinical practice, we attempted to synthesize the motivations and resistances, and investigate their mutual relationships for advancing the implementation of SDM. Methods A comprehensive systematic review using Preferred Reporting Items for Systematic Review and Meta‐Analysis guidelines was performed. 'Shared decision making' was searched as the mesh term through PubMed, Web of Science and EBSCO from 2000 to 2021, and the quality of literature was appraised using the QualSyst Tool. Motivations and resistances were categorized based on content analysis and the 'structure-process-outcome' model. Results From 8319 potential citations, 105 were included, comprising 53 qualitative studies (the average quality score is 0.92) and 52 quantitative studies (the average quality score is 0.95). A total of 42 categories of factors were identified into 11 themes and further grouped into three dimensions: structure, process and outcome. The structure dimension comprised six themes (71.43%), the process dimension contained four themes (11.01%) and the outcome dimension covered only one theme. Across all categories, decision‐making time and patients' decision preparedness in the process dimension were the most reported, followed by physicians' communication skills and health care environment in the structure dimension. Analysis of implementation of SDM among various types of diseases showed that more influencing factors were extracted from chronic diseases and unspecified disease decisions. Conclusions The major determinants for the implementation of SDM are focused on the structural dimension, which challenges the health systems of both developed and low‐ and middle‐income countries. Furthermore, we consider it important to understand more about the interactions among the factors to take integrated measures to address the problems and to ensure the effectiveness of implementing SDM. Patient or Public Contribution Patients, healthcare professionals and other stakeholders articulated their perspectives on the implementation of SDM actively, and these were adopted and analysed in this study. However, the above‐mentioned individuals were not directly involved in the process of this study. Protocol was registered on PROSPERO (CRD42021259309).